Effect of trophic support on the dynamics of growth processes and carbohydrate content of winter wheat sprouts under vernalization - Chumakova, V.; Avksentieva, O. (The Journal of V.N.Karazin Kharkiv National University. Series «Biology», 2019)
The influence of contrasting conditions of trophic support of vernalization on the growth reaction and dynamics of the content of various fractions of soluble carbohydrates of sprouts of two winter wheat varieties Statna and Doridna were studied. In experiments, the contrasting trophic conditions of vernalization were created by adding 3% sucrose solution, as well as isolation of endosperm, a natural reserve of carbohydrates and biologically active substances. It was shown that optimal conditions of trophic support (integral seeds + water) determined the maximum linear growth and accumulation of sprouts biomass during vernalization. The excess of exogenous sugars (integral seeds + 3% sucrose solution) inhibited growth processes. However, the deficit of trophic factors (isolated buds + 3% sucrose solution) also inhibited growth and the lack of trophic support (isolated buds + water) completely inhibited growth and accumulation of sprouts biomass during 45 days of vernalization. It was established that the dynamics of changes in soluble carbohydrates content in winter wheat sprouts also depended on the trophic support level of vernalization and correlated with changes of growth reaction. It was shown the oligosaccharide content was significantly higher than monosaccharide content of sprouts of all the variants of both varieties during the entire period of vernalization. In view of the fact that monosaccharides are the most metabolically active carbohydrates, they are probably spent as much as possible at the first stages of vernalization (15–30 days). It is discussed that different level of trophic support is able to be one of the important factors of genetic and/or epigenetic regulation of Triticum aestivum L. Thus, changes in metabolic processes, in particular carbohydrate metabolism, can effect on the reduction of VRN genes expression, which are the target of epigenetic regulation, and as a result, on the ability of soft wheat plants to flower. It is assumed that the regulatory role of carbohydrates in vernalization process can be realized only at the optimal level of trophic support.